Cellular and molecular characterization of an embryonic cell line (BME26) from the tick Rhipicephalus (Boophilus) microplus - Esteves, Eliane; Lara, Flavio A.; Lorenzini, Daniel M.; Costa, Gustavo H. N. [UNESP]; Fukuzawa, Aline H.; Pressinotti, Luis N.; Silva, Jose Roberto M. C.; Ferro, Jesus A. [UNESP]; Kurtti, Timothy J.; Munderloh, Ulrike G.; Daffre, Sirlei (Pergamon-Elsevier B.V. Ltd, 2008)
The cellular and molecular characteristics of a cell line (BME26) derived from embryos of the cattle tick Rhipicephalus (Boophilus) microplus were studied. The cells contained glycogen inclusions, numerous mitochondria, and vesicles with heterogeneous electron densities dispersed throughout the cytoplasm. Vesicles contained lipids and sequestered palladium meso-porphyrin (Pd-mP) and rhodamine-hemoglobin, suggesting their involvement in the autophagic and endocytic pathways. The cells phagocytosed yeast and expressed genes encoding the antimicrobial peptides (microplusin and defensin). A cDNA library was made and 898 unique mRNA sequences were obtained. Among them, 556 sequences were not significantly similar to any sequence found in public databases. Annotation using Gene Ontology revealed transcripts related to several different functional classes. We identified transcripts involved in immune response such as ferritin, serine proteases, protease inhibitors,. antimicrobial peptides, heat shock protein, glutathione S-transferase, peroxidase, and NADPH oxidase. BME26 cells transfected with a plasmid carrying a red fluorescent protein reporter gene (DsRed2) transiently expressed DsRed2 for up to 5 weeks. We conclude that BME26 can be used to experimentally analyze diverse biological processes that occur in R. (B.) microplus such as the innate immune response to tick-borne pathogens. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Tick; embryonic cells; Immunity; Transfection; Sleeping beauty; DsRed2 gene